Efektivitas Mediasi sebagai Instrumen Penyelesaian Sengketa Kewarisan dalam Perkara No. 703/Pdt.G/2024/PN Mdn - Moh Ibnuh Ubaidillah (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2026)
This study examines the resolution of Civil Case No. 703/Pdt.G/2024/PN Mdn, focusing on the determination of lawful heirs and the implementation of mediation as an alternative dispute resolution mechanism in inheritance cases. The research applies a normative juridical method with a qualitative approach, utilizing court decisions, statutory regulations, and relevant legal literature as sources of analysis. The findings indicate that mediation successfully facilitated a mutually accepted agreement between the disputing parties, which was subsequently formalized and ratified by the court through a legally binding Deed of Settlement. Compared with conventional litigation procedures, mediation proved to be more efficient in terms of time, cost, and procedural complexity while preserving harmonious family relationships among the heirs. The court’s ruling further provided legal certainty regarding the identification of lawful heirs, the distribution of inherited assets, and the allocation of procedural costs. Therefore, this case demonstrates that mediation constitutes an effective, practical, and socially constructive approach to resolving inheritance disputes while ensuring legal certainty, fairness, and long-term family harmony.